Association between nuclear factor of activated T cells C2 polymorphisms and treatment response in rheumatoid arthritis patients receiving tumor necrosis factor-alpha inhibitors. Issue 1 (January 2022) - Kim, Woorim; Kim, Hyun Jeong; Trinh, Nga Thi; Yeon, Ha Rim; Kim, Joo Hee; Choi, In Ah; Kim, Hyoun-Ah; Jung, Ju-Yang; Lee, Kyung Eun
Abstract : Objectives: Nuclear factor of activated T cells C2 (NFATC2) is known as a member of the transcription family and enhances tumor necrosis factor-alpha (TNF-α) synthesis in human T cells at the gene transcription level. Although NFATC2 has a potential role in rheumatoid arthritis (RA) progression and treatment, no study has investigated the association between NFATC2 gene polymorphisms and response status in RA patients receiving TNF-α inhibitors. This study aimed to examine the effects of polymorphisms in NFATC2, a TNF-α transcription factor, on response to TNF-α inhibitors. Methods: This prospective observational study was performed in two centers. Seven single nucleotide polymorphisms (SNPs) were investigated. Good responders were defined as patients with disease activity score (DAS)28 ⩽3.2 after 6 months of treatment. Logistic regression analyses were used to investigate the association between genetic polymorphisms and response to the treatment. To test the model's goodness of fit, a Hosmer–Lemeshow test was performed. Results: This study included 98 patients, among whom 46 showed favorable responses to the treatment. Patients with hypertension revealed an approximately three-fold lower response to TNF-α inhibitors compared to those without hypertension (23.5 vs. 76.5%; P = 0.049). After adjusting for covariates, C allele carriers of NFATC2 rs3787186 exhibited approximately three-fold lower rates of treatment response compared to those with TT genotype ( P = 0.037). The Hosmer–Lemeshow test showed that the fitness of the multivariable analysis model was satisfactory (χ 2 = 9.745; 8 degrees of freedom; P = 0.283). Conclusion: This study suggested an association between the C allele of rs3787186 and treatment response in RA patients receiving TNF-α inhibitors.